Detection of Mycobacterium avium subsp. paratuberculosis in Cow Milk Using Culture and PCR methods - rezavand, B. (Archives of Razi Institute, 2011)
Mycobacterium avium subspecies paratuberculosis (MAP) is the cause of John’s disease also calledparatuberculosis. This is economically one of the important infectious diseases in cattle and ruminanthusbandry. This disease is manifested as granulomatosis entrocolitis, lymphadenitis and inflammation locallymphatic vessels. The typical sign of this disease is progressive loss of weight. Considering the importanceof detection of this disease in this study, two methods, culture and PCR, were used for the identification ofthis microorganism. In this study 100 milk samples from apparently healthy cows and 100 milk samplesfrom cows that have been suspicious of John’s disease were taken from in Sarab, East Azarbaijan, Iran.Direct microscope observation after ziehl-neelsen staining was done. Then, bacterial culture on specificmedium was carried out, and finally, identification of Mycobacterium avium subsp. paratuberculosis wasexamined using PCR and specific primers. Using direct observation, culture and PCR analyses showed thatfrom 100 healthy cow milk samples, 8, 9 and 12 samples were positive MAP for each method respectively.The results of direct observation, culture and PCR analysis on affected cows were 15, 40 and 44, respectively. The results of this study showed that culture and PCR analyses methods are important in the identification of the causes of this disease. Therefore, considering the frequency of the disease in the studied region, either of those methods can be used in the microorganism identification.